PENGARUH SENAM HAMIL TERHADAP KUALITAS TIDUR IBU HAMIL TRIMESTER III DI PMB K TAHUN 2022 - Girsang, Rut Yohana (Politeknik Tiara Bunda, 2022)
Background: Stunting is a nutritional status based on the Length or Height According to Age index with a z-score of <-2 Standard Deviation (SD). The case of stunting toddlers in Karangasem Village in March 2021 was 21.62%. The results of interviews with 10 respondents found that 60% of them, or 6 of them, had low education. Previous research on the relationship between maternal knowledge, education, and feeding parenting with stunting incidence in toddlers has been carried out with a cross- sectional design. Objective: The purpose of this study was to determine the relationship between knowledge, education, and parenting patterns of feeding with the incidence of stunting in toddlers in Karangasem Village, Bulu District, Rembang Regency. Method: This study is an observational analytical quantitative research with a case-control research design. The sampling technique was obtained through total sampling with consideration of matching residential addresses, namely a total sample of 40 consisting of 20 case samples (stunted toddler mothers) and 20 control samples (non-stunted toddler mothers). Stunting data were obtained through anthropometric methods, while educational data, knowledge, and feeding parenting data were obtained through questionnaires with the help of interviewmethods. Bivariate analysis used the McNemar test for the 2x2 table and Wilcoxon for the 2x table >2. Results: The group of stunted who had sufficient & low category knowledge was 15 (75%) respondents and in the non-stunted group 6 (30%) respondents. The group of stunted who had basic category education was 15 (75%) respondents and in the non- stunted group 13 (65%) respondents. The group of stunted cases in which the application of feeding parenting was included in the bad category was 15 (75%) respondents and in the non-stunted group 16 (80%) respondents. The results of the bivariate analysis found a relationship between maternal knowledge and the incidence of stunting in toddlers (p = 0.00, OR = 2.00), and there was no relationship between maternal education (p = 0.70) and feeding parenting (p = 1.00) with the incidence of stunting in toddlers in Karangasem Village, Bulu District, Rembang Regency. Conclusion: Maternal knowledge is a factor related to the incidence of stunting in toddlers in Karangasem Village, Bulu District, Rembang Regency (p = 0.00; OR = 2.00).